If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -7 = 36 Reorder the terms: -7 + z = 36 Solving -7 + z = 36 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + z = 36 + 7 Combine like terms: -7 + 7 = 0 0 + z = 36 + 7 z = 36 + 7 Combine like terms: 36 + 7 = 43 z = 43 Simplifying z = 43
| 2-(1/4) | | (5x)+(x+20)+(2x)=180 | | 4+9(x)=184 | | (9*sqr-1)8(-6*sqr-4)= | | 20=x-4 | | w-50=16 | | -14=(6/7)x-4-7x | | (9*((-1)^1/2)*((-6)((-4)^1/2))= | | 6x-7=1+4x | | 47=p+14 | | 0.04(y-8)+0.02y=0.16y-0.9 | | -14=(6/7x)-4-7x | | 10x=3+12 | | (3w^2-7w+2)+(-4w^2+5w+1)= | | 5x-(7)=7x-(17) | | -3x-6=18forx | | 10x+4x+3+7=9x+3+4x | | 18=3d | | 8=(10)w(2) | | ln(y)=2ln(x)+ln(10) | | 23x+21x=72 | | h-23=27 | | 9i*12i= | | 2(x+1)+5=-4(x-2) | | 5(3x+7)=-19+39 | | 17+p=30 | | 4+5lnx=19 | | 5u^3+4u^2-25u-20=0 | | 5(5x+2)-5= | | 4(-6x-2)+10=8(-3x-1)+14 | | n/-20=0 | | -4(15y+1)+8=20(-3y+5)-102 |